Leading without greed: A Vedantic lens on wholeness toward cultivating spiritual intelligence in leadership - Maharaj, Nerisha (Graduate School of Business (GSB), 2024)
As the current civilisation grapples with existential grand challenges, it is suggested that old leadership paradigms furthering social injustice and environmental crises through greed, be examined. Greed was theorised in the literature as arising from a material ‘incomplete self' predicament of constant want. Vedānta posits such never-ending desiring to be consequential of a lack of spiritual intelligence. Systematic reviews into workplace spirituality studies identified a need for qualitative leadership research, specifically recommending Eastern spiritual lenses, due to rising interest. Wholeness is central to spirituality, considered fundamental to human flourishing, yet remains nascent. This study explored whether wholeness, as conceptualised from a Vedāntic lens, could be meaningful for cultivating spiritual intelligence in leadership outside a Vedāntic context. Applying a Vedāntic lens, three essential constructs of wholeness were identified, namely, Being, consciousness, and joy. Hermeneutical phenomenology was applied through semi-structured interviews with twentyfive purposively sampled leaders across diverse sectors and spiritual orientations. The findings were triangulated across two different focus groups comprising fifteen participants, thus totalling forty study participants. Data analysis was conducted through transcript coding and thematic categorisation. Wholeness, as conceptualised, was found both meaningful and relatable outside a Vedāntic context by both spiritually active and not so spiritually active leaders, who expressed cognitive and emotional resonance with the constructs in relation to wholeness. Moreover, the findings showed such wholeness to be holistically meaningful for spiritual intelligence in leadership, encompassing leadership of both self and others, with positive organisational and social macro-implications. Leaders felt that wholeness through Being, consciousness, and joyful contentment would evoke less greed in leadership, greater virtues-orientation, holistic consciousness in decision-making, and a more human-centric approach to leadership, since a sense of inner completeness evokes fewer desires and greater contentment. Potential societal and organisational macro-implications included holistic business models and kinder, equitable societies. The findings offered a practical way to cultivate spiritual intelligence toward addressing greed and the incomplete self, contributing toward the nascent concept of wholeness whilst encouraging the inclusion of multi-cultural perspectives. The study contributed three novel, meaningful wholeness constructs with phenomenological insights on leadership import, a Vedāntic Leadership Model of Wholeness incorporating a Whole Self theory, and epistemological findings on the processual interplay between the Whole Self and incomplete self.